Motor competence in preschool children's: An analysis in private and public school children - Daniel da Rocha Queiroz; Rafael dos Santos Henrique; Anderson Henry Pereira Feitoza; Jéssica Nayara Silva de Medeiros; Cleverton José Farias de Souza; Teresinha de Jesus Sousa Lima; Maria Teresa Cattuzzo (Desafio Singular, 2017)
The objective of this study was to compare the motor competence of children in different environments, namely private and public schools. This study looked at a representative sample of preschool children (3-5 years) the city of Recife-PE. We included all subjects who completed the Test of Gross Motor Development - 2. The groups were made up of children from private schools (n = 161; 95 boys), and public (n = 131; 63 boys). Data analysis used analysis of variance (ANOVA Two-Way), by adopting a p ≤ 0.05. In general, private school children had superior performance. When analyzed gender differences, boys were higher. The results suggest that children of different school environments appear to differ in their motor competence. Therefore, we suggest that future studies assessing the characteristics of space used and the intensity and duration of activities that children are involved.